Presence of diminutive hadrosaurids (Dinosauria: Ornithopoda) from the Maastrichtian of the south-central Pyrenees (Spain) - Company, J.; Cruzado-Caballero, P.; Canudo, J.I. (Journal of Iberian Geology, 2015)
In recent years a rich and diverse fauna of hadrosaurid dinosaurs has been described in the Upper Cretaceous of the Pyrenees. Recent fieldwork carried out in the upper Maastrichtian levels of the Tremp Formation, in the south-central Pyrenees (province of Huesca, northeastern Spain), has allowed us to recover diminutive fossil bones referable to hadrosaurid dinosaurs. To date, small-sized specimens had not been reported in the area. The remains consist of small vertebrae and fragmentary long bones found in a relatively small area, so it is assumed that they probably belong to individuals of a single population. A morphological examination and a histological study reveal that they represent specimens of advanced ontogenetic stage and allow the identification of an undescribed taxon of small-bodied hadrosaurids. In other parts of Europe, discoveries of small dinosaurs have been linked to insularity. These findings bring to light the smallest hadrosaurid known in Europe to date.